Deep Inferior Epigastric Artery Perforator Flap Breast Reconstruction in Women With Previous Abdominal Incisions: A Comparison of Complication Rates. Issue 5 (November 2018) - Doval, Andres F.; Lamelas, Andreas M.; Daly, Lauren T.; Tobias, Adam M.; Lin, Samuel J.; Singhal, Dhruv; Dowlatshahi, Arriyan Samandar; Lee, Bernard T.
Abstract : Background: The deep inferior epigastric artery perforator (DIEP) flap is currently the most widely used method for autologous microsurgical breast reconstruction. There are mixed data in the literature regarding the impact of previous abdominal surgery on DIEP flap success in breast reconstruction. With this study, we take a closer look at the effect of prior abdominal surgery on DIEP flap and donor-site complications, with a particular focus on the different types of incisions and their influence on surgical outcomes. Methods: A retrospective cohort study was conducted over a 6-year period. Five hundred forty-four consecutive DIEP flaps were divided into a control group (321 flaps) without previous abdominal surgery and an incision group (223 flaps) with previous abdominal surgery. A comparison between both groups was made in terms of flap and donor-site complications followed by a subgroup analysis based on single types of abdominal incisions. Results: There were no significant differences between both groups in terms of age, body mass index, flap weight, smoking history, prior radiotherapy, diabetes, and coagulopathy ( P > 0.05). The most common incision was low transverse incision (n = 116) followed by laparoscopy port (n = 103) and midline (n = 46) incisions. We found no significant differences between the control group and incision group in terms of flap complications. Subgroup analysis revealed that none of the 3 types of incision increase the flap or donor-site complications. Smoking and flap weight were the only 2 independent predictors for donor-site complications. Conclusions: The results from this large series of consecutive DIEP flaps from our institution confirm that autologous breast reconstruction with DIEP flap can be safely performed in patients who have had previous abdominal surgeries; however, counseling patients about smoking is critical to avoid potential donor-site complications.